High-speed path following control of skid-steered vehicles. (August 2019) - Huskić, Goran; Buck, Sebastian; Herrb, Matthieu; Lacroix, Simon; Zell, Andreas
We present a robust control scheme for skid-steered vehicles that enables high-speed path following on challenging terrains. First, a kinematic model with experimentally identified parameters is constructed to describe the terrain-dependent motion of skid-steered vehicles. Using Lyapunov theory, a nonlinear control law is defined, guaranteeing the convergence of the vehicle to the path. To allow smooth and accurate motion at higher speeds, an additional linear velocity control scheme is proposed, which takes actuator saturation, path following error, and reachable curvatures into account. The combined solution is experimentally evaluated and compared against two state-of-the-art algorithms, by using two different robots on several different terrain types, at different speeds. A Robotnik Summit XL robot is tested on three different terrain types and two different paths at speeds up to≈ 2 . 5 m/s. A Segway RMP 440 robot is tested on three different terrain types and two different path types at speeds up to≈ 6 m/s.